Extrusion problems solved : food, pet food and feed - Riaz, Mian N.; Rokey, Galen J. (Woodhead Publishing in food science, technology, and nutrition, 2012)
Extrusion is widely used for the preparation of a variety of foodstuffs including breakfast cereals, snack food and pasta, as well as pet food and animal and aquaculture feed. Extrusion problems solved provides responses to more than 300 frequently asked questions about the process of food extrusion and the techniques and equipment involved, in a practical question-and-answer format. The book is divided into twelve chapters for ease of reference: the opening chapters concentrate on introductory queries and on different components of an extruder system, followed by two chapters that help the reader select the correct type of extruder for a product. Chapters five and six discuss the impact of factors such as protein content and particle size on the extrusion process, while the use of pre-conditioners is discussed in chapter seven. The latter part of the book discusses specific types of extruder and die and knife assemblies, followed by a chapter on issues relating to drying extruded food products. The final chapter offers practical guidelines and rules of thumb for the most common issues relating to food and feed extrusion. Written by two leading experts in the field, Extrusion problems solved is an essential reference source and troubleshooting guide for professionals working in food, pet food and feed extrusion. It will also be a valuable training resource for students of extrusion. Offers practical guidelines and rules of thumb for the most common food and feed extrusion problemsChapters concentrate on introductory queries, types of extruder and components of extruder systems, knife assemblies, the use of pre-conditioners and issues in drying extruded food productsProvides responses to more than 300 frequently asked questions about the processes, equipment and techniques of food extrusion in a practical question-and-answer format.